STUDI KOMPARASI METODE A BA TA TSA DAN IQRA DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN (PENELITIAN DI SDIT AL FITRAH RANCASARI BANDUNG) - Riza Pratama; Wati Karmila (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Agama Islam YAPTIP Chadijah Ismail Pasaman Barat, 2020)
The purpose of this study is to find out how to compare the abilityto read the Qur'an using the A Ba Ta Tsa and Iqra methods of students inSDIT Al Fitrah, Manjahlega Village, Rancasari District, Bandung City.This study uses a quantitative approach and in the collection of data usedobservation and test methods. The data analysis technique iscomparative data analysis with t-test testing using the Separated Varianformula that compares the ability to read the Qur'an by using the Iqraand A Ba Ta Tsa methods for students. The results of data analysisshowed that the t count was 0.95. With a significant level ἀ = 0.05 due tothe two-tailed test, the value of ἀ / 2 = 0.05 / 2 = 0.025. then look for atable in the t-distribution table with the provisions: db = n-2, db = 34-2= 32 so t (ἀ, db) = t (0.025, 32) = 2,042. In this case, the provisionsapply that if -table